Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Adjusting the Structure and Electronic Properties of Carbons for Metal‐Free Carbocatalysis of Organic Transformations - Antonietti, Markus; Lopez Salas, Nieves; Primo, Ana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine

Effectuation, entrepreneurs' leadership behaviour, and employee outcomes: a conceptual model - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Internet of Things Architecture for Handling Stream Air Pollution Data - Kersting, Joschka; Geierhos, Michaela; Jung, Hanmin; Kim, Taehong (Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security)
In this paper, we present an IoT architecture which handles stream sensor data of air pollution. Particle pollution is known as a serious threat to human health. Along with developments in the use of wireless sensors and the IoT, we propose an architecture that flexibly measures and processes stream data collected in real-time by movable and low-cost IoT sensors. Thus, it enables a wide-spread network of wireless sensors that can follow changes in human behavior. Apart from stating reasons for the need of such a development and its requirements, we provide a conceptual design as well as a technological design of such an architecture. The technological design consists of Kaa and Apache Storm which can collect air pollution information in real-time and solve various problems to process data such as missing data and synchronization. This enables us to add a simulation in which we provide issues that might come up when having our architecture in use. Together with these issues, we state r easons for choosing specific modules among candidates. Our architecture combines wireless sensors with the Kaa IoT framework, an Apache Kafka pipeline and an Apache Storm Data Stream Management System among others. We even provide open-government data sets that are freely available.
Keywords: Wireless Sensor Network; Internet of Things; Stream Data; Air Pollution; DSMS; Real-time Data Processing

Reciprocation Effort Games - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: interaction; reciprocation; contribute; shared effort; curbing; convergence; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Competition between Cooperative Projects - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: agents; projects; contribute; shared effort game; competition; quota; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Sievers, Sönke; Klobucnik, Jan; Miersch, David
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation